(untitled) (Research, Society and Development, 2021)
Objective: to evaluate the risk factors for osteoporosis and fragility fracture in elderly women. Methods: Descriptive, observational and cross-sectional study with a convenience sample carried out in an outpatient, private service, linked to the Tiradentes University, in the city of Aracaju-SE. Results: The study sample consisted of 102 post-menopausal women. The three risk factors for osteoporosis that were more frequent in our sample were sedentary lifestyle (70.6%), use of corticosteroids (17.6%), early menopause (15.3%), all participants had at least three factors risk. All study participants have an indication for bone densitometry, however 68 (66.7%) reported having undergone the examination and of these, 32 (31.4%) reported having a diagnosis of densitometric osteoporosis. Regarding the fall, 43 (42.2%) participants reported having had at least one episode in the last year. Conclusions: Our results demonstrate that the female and elderly population, although presenting greater risk for osteoporosis and fragility fracture, is still neglected in our country, demonstrating that there is a need for health promotion programs and routine medical practice to detect the factors of risk for osteoporosis and fractures in the groups of individuals most likely to have these clinical conditions.